2018
DOI: 10.3390/bios8010013
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Corrosion Stability of a Microchip Sensor Implant during In Vivo Exposure

Abstract: A microelectronic biosensor was subjected to in vivo exposure by implanting it in the vicinity of m. trapezii (Trapezius muscle) from cattle. The implant is intended for the continuous monitoring of glucose levels, and the study aimed at evaluating the biostability of exposed semiconductor surfaces. The sensor chip was a microelectromechanical system (MEMS) prepared using 0.25 µm complementary metal–oxide–semiconductor CMOS/BiCMOS technology. Sensing is based on the principle of affinity viscometry with a sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In addition, the development and test of implantable biosensors has to overcome high administrative obstacles, since human body implants are meaningfully subjected to strict regulations via various laws and enactments [ 10 ]. This holds in a comparable manner for animal models that are frequently used for preliminary tests of human medical implants [ 12 , 13 ]. One of these requirements relates to the sterilization of the implant that has to be demonstrated prior to any in vivo testing.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, the development and test of implantable biosensors has to overcome high administrative obstacles, since human body implants are meaningfully subjected to strict regulations via various laws and enactments [ 10 ]. This holds in a comparable manner for animal models that are frequently used for preliminary tests of human medical implants [ 12 , 13 ]. One of these requirements relates to the sterilization of the implant that has to be demonstrated prior to any in vivo testing.…”
Section: Introductionmentioning
confidence: 82%
“…Previous investigations have shown that the exposed surfaces from TiN [ 16 , 17 ], SiO 2 , and SiON remain intact in vitro and would allow sensor chip operation in liquid environments for many months [ 13 , 18 ]. It is shown here how the developed BioMEMS can be integrated into a hermetically sealed implant.…”
Section: Introductionmentioning
confidence: 99%